«TO LOVE YOUR NEIGHBOR AND TO FEEL SORRY FOR HIM… JUST BECAUSE»: PERSONALITY AND THE WORLD IN THE COLLECTION OF POETRY BY GALINA FELIKSON AND OLEG GONCHARENKO «REFLECTION. REFLEXION» - Zaidler, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article of N. V. Zaidler «To love your neighbor and to feel sorry for him… just because»: personality and the world in the collection of poetry by Galina Felikson and Oleg Goncharenko «Reflection. Reflexion» is researched the poetry and translations of the Israel and Ukrainian writers in terms of reflection of such problems as active life position of the individual, the place and role of the poet in society, contemporary level of morality of people etc. It is emphasized that poets call mankind to live in peace and profess God's commandments.